The abused child: plaintiff and witness in the trial. Secondary victimization as a source of damage and the new aspects of compensation starting with the decision of the Sezioni Unite, November 11, 2008, No. 26972 - Abus sur mineur: partie offensée et témoin dans le procès pénal. La victimisation secondaire comme source de dommage et les nouvelles frontières de l’indemnisation ouvertes par les Chambres Unies le 11 novembre 2008, n° 26972 - Il minore abusato: parte offesa e testimone nel processo penale. La vittimizzazione secondaria quale fonte di danno e le nuove frontiere del risarcimento aperte dalle Sezioni Unite 11 novembre 2008, n. 26972 - Toni C. (Rivista di Criminologia, Vittimologia e Sicurezza, 2009)
The role of the offended person’s deposition, possibly the only proof in case of abuse, may involve dynamics which do not consider the needs of the victim himself, and so causing "secondary victimization". Then, especially when further care is required during investigation if the victim is a child, the situation can worsen the already traumatic consequences of the abuse, due to the violence of the trial, which appears to be regardless of the appropriate time for the hearing. Consequently, this damage should not be ignored during the calculation of all-comprehensive compensation, and should conform with the latest jurisprudence of the “Sezioni Unite” of “Cassazione Civile”.